Biogas production from bioethanol waste: the effect of pH and urea addition to biogas production rate - Budiyono Budiyono; Iqbal Syaichurrozi; Siswo Sumardiono (Diponegoro University, 2013)
Anaerobic treatment is a good choice to treat bioethanol waste due to the high concentration of COD content for producing biogas as renewable energy. The purposes of this study were to study the effect of addition nitrogen source and pH control to biogas production. The laboratory scale-anaerobic digestions used in this experiment were operated in batch system and at room temperature. In determination of optimum pH, bioethanol waste and rumen fluid fed into digesters with initial pH 6.0; 7.0 and 8.0. Influent COD : N ratio (in form of urea) used in this study was 700:7 in compare to control. The results showed that initial pH 7.0 produced the most biogas with total biogas 3.81 mL/g COD. While initial pH 6 and pH 8 had total biogas 3.25 mL/g COD and 3.49 mL/g COD respectively. At urea addition, biogas formed had 52.47% greater than that of at without urea addition (control variable). Controlled pH caused biogas was produced until 90-day investigation and might continue to be produced. Total biogas of control variable (without urea addition) and variable with ratio COD:N=700:7 influent were 11.07 mL/g COD and 11.41 mL/g COD respectively.Doi: http://dx.doi.org/10.12777/wastech.1.1.1-5Citation: Budiyono, Syaichurrozi, I. and Sumardiono, S. 2013. Biogas production from bioethanol waste: the effect of pH andurea addition to biogas production rate. Waste Technology 1(1):1-5. Doi: http://dx.doi.org/10.12777/wastech.1.1.1-5